Clinical characteristics of patients seeking medical advice for nasal symptoms in Bulgaria with special focus on children. Issue 1 (December 2016) - Mustakov, Tihomir; Popov, Todor; Kralimarkova, Tanya; Staevska, Maria; Dimitrov, Vasil
Abstract Background In an attempt to circumvent low response rates and high cost of classical epidemiological trials, we carried out a real-life survey among practicing physicians consulting patients for nasal symptoms. In this fragment of our work we analyze similarities and differences between children and adults and within the different strata of pediatric age. Methods A survey was carried out by 69 physicians across Bulgaria (general practitioners, allergists and otorhinolaryngologists) and made possible calculation of the proportion of subjects with nasal symptoms from all other patients seen. Its structure allowed classification of rhinitis according the ARIA guidelines. Results Out of the 1685 completed survey forms, 506 pertained to the age group below 18 years. The gender predominance differed in children and adults: 57.3 % vs. 42.8 % of males respectively, P  < 0.001. The prevalence of persistent rhinitis in children was 55.7 %, lower than in adults, 63.3 %, P  = 0.004. In both pediatric and adult patients moderately severe and severe forms of rhinitis prevailed, 93.7 % vs. 94.6 %, with nasal obstruction as leading symptom: 59.9 % vs. 58.8 %. Cough was significantly more prevalent among children, 72.5 %, gradually decreasing until reaching adulthood, 58.7 %, P  < 0.001. Prevalence of doctor diagnosed asthma was also higher among children, 25.1 %, than in adults, 19.5 %, P  = 0.011. A gradient for characteristics, which were different in children, emerged across the pediatric age strata. Discussion Our study uses an unorthodox design targeting the patient population visiting physicians' offices because of nasal symptoms, achieving a much higher level of credibility of the results at minimal expense. As we base our survey on international guidelines, we believe this approach demonstrates the applicability of such consensus documents for practical purposes when in the hands of qualified physicians. Conclusions Moderate and severe rhinitis symptoms motivate patients and their guardians to seek medical advice. While nasal congestion is a leading bothersome symptom in both adults and children, specific other features characterize the pediatric age and differ across its strata.